When a "One Size" Model Doesn't Fit All: The Building Healthy Schools Program. Issue 2 (12th February 2019) - Hivner, Elizabeth; Hoke, Alicia; Francis, Erica; Ricci, Tiffany; Zurlo, Claire; Kraschnewski, Jennifer
Abstract : Although research suggests various effective interventions to curb obesity, there remains a gap between current evidence and sustainable practice in schools and communities. School settings present a logical platform for this work, since children spend much of their time in school. This article describes the Building Healthy Schools Program, a school-based partnership model that builds on the comprehensive school physical activity program framework by incorporating technical assistance and components of the Whole School, Whole Community, Whole Child model. The Building Healthy Schools Program aligns with the current school structure by utilizing wellness councils to plan and implement evidence-based obesity-prevention strategies over a two-year period. Participating school districts focus on creating and sustaining quality physical activity and nutrition environments by developing a strong wellness-council foundation and through policy revision. The utilization of evidence-based models, alignment with the standard school structure, and flexibility to meet districts "where they are" makes it possible for any school district to replicate the program, effectively connecting the gap between obesity-prevention research and community practice.